PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN AGROFORESTRI JAGUNG HIBRIDA DI HUTAN GUNUNG GEULIS KABUPATEN SUMEDANG - Hidayat, Yayat; Ruswandi, Dedi; Rumidatul, Alfi (Abdi Panca Marga, 2024)
To fulfill the requirements for livestock feeding, the nearby communities of the Geulis forest gather gmelina leaves and sobsi, resulting in the deterioration and collapse of trees, consequently disrupting the long-term viability of the forest. In order to resolve this problem, we must identify a sustainable livestock feed solution and strengthen our efforts to conserve forests. One approach involves cultivating shade-tolerant hybrids of corn within agroforestry systems. There is currently a lack of widespread awareness regarding the specific varieties of corn plants that possess the ability to tolerate shade. Consequently, it is imperative to demonstrate commitment to the local community in the Mount Geulis forest region. Surveys, focus group discussions, design, training, monitoring, and evaluation are the methods employed for dedication activities. We are committed to improving the community's knowledge and abilities in growing shade-tolerant hybrid corn through the agroforestry method, as well as utilizing corn waste for livestock feed. References Atmanto, W.D., Suryanto, P., Adriana, Triyogo, A., Faridah, E., Prehaten, D., Budiadi. (2023). Optimalisasi Penggunaan Lahan dengan Sistem Agroforestri di Desa Ngancar, Ngawi. PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat. 8(2): 195–204. https://doi.org/10.33084/pengabdianmu.v8i2.3938 Fardiansyah, D., Kusuma, A.B., Pathiassana, M.T. (2022). Kajian Penerapan Model Agrosilvopastura dalam Peningkatan Kesejahteraan dan Pendapatan Kelompok Tani Hutan Sorowua Desa Paradowane Kecamatan Parado. Jurnal Tambora, 6(2), 66–77. https://doi.org/10.36761/jt.v6i2.2004 Fariz, T.R., Ihsan, H.M., Lutfiananda, F., Sartohadi, J., Darmajati, Y., & Syahputra, A. (2023). Perbandingan pengukuran kerapatan kanopi dari hemispherical photography dan UAV untuk pemetaan menggunakan citra sentinel-2. Jurnal Hutan Tropis, 11(1), 123–132. http://dx.doi.org/10.20527/jht.v11i1.16000 Hadiyane, A., Rumidatul, A., Hidayat, Y. (2021). Aplikasi Teknologi Biopelet Limbah Kopi sebagai Bahan Bakar Alternatif dalam Rangka Pengembangan Desa Mandiri Energi di Desa Jatiroke Kawasan Sekitar Hutan Pendidikan Gunung Geulis ITB. Jurnal Panrita Abdi, 5(3), 256–265. https://doi.org/10.20956/pa.v5i3.9536 HS, H.H., Ariyanto, S.E., & Sudjianto, U. (2021). Pemberdayaan masyarakat melalui penerapan agroforestri pada lahan kritis di Desa Wonosoco Kacamatan Undaan Kabupaten Kudus. Muria Jurnal Layanan Masyarakat, 3(2), 111–118. https://doi.org/10.24176/mjlm.v3i2.5708 Rajagukguk, C.P., Febryano, I.G., & Herwanti, S. (2018). The change of plant species composition and plant pattern on management of damar agroforestry. Jurnal Sylva Lestari, 6(3), 18–27. https://doi.org/10.23960/jsl3618-27 Ruswandi, D., Azizah, E., Maulana, H., Ariyanti, M., Nuraini, A., Poppy Indriani, N., Yuwariah, Y., Indriani, N. P., & Yuwariah, Y. (2022). Selection of high-yield maize hybrid under different cropping systems based on stability and adaptability parameters. Open Agriculture, 7(1), 1–10. http://dx.doi.org/10.1515/opag-2022-0073 Safitri, F.D., Pambudi, M.D., Haris, A. (2023). Peningkatan Kesejahteraan Petani melalui Program Agroforestri Sengon, Jagung dan Kopi di Desa Gunungsari, Kabupaten Kebumen. Jurnal Dharma Indonesia, 1(2), 44–51. https://doi.org/10.15294/jdi.v1i2.68875 Wijayanto, H.W., Lo, K.A., Toiba, H., & Rahman, M.S. (2022). Does agroforestry adoption affect subjective well-being? empirical evidence from smallholder farmers in East Java, Indonesia. Sustainability, 14(16), 10382. https://doi.org/10.3390/su141610382 Yundari, N.K.W., Karmau, J.J., Arisena, G.M.K. (2022). Kajian Kelayakan Finansial Kawasan Agroforestry. Benchmark, 2(2), 151–163. https://doi.org/10.46821/benchmark.v2i2.267